MINICONTO READING AND INTERPRETATION: DEVELOPMENTS OF SENSES - Silveira Galli, Fernando Correa [UNESP]; Souza, Andreia Dias de [UNESP] (Univ Estado Mato Grosso, 2020)
The flash fiction can be defined as a short textual genre that presents, among other characteristics, the ellipse or hidden history as a constituent; this text has gained popularity both in collections and on virtual platforms and has been the subject of several studies of a literary nature (LAGMANOVICH, 2006; PAULINO, 2004; SPALDING, 2008; CASCALES, 2013). The revelation of history is directly linked to interpretation, which allows us to discuss the characteristics attributed, by scholars, to this genre and present a reflection on the process of reading and interpreting flash fiction, based on the discursive approach (ORLANDI, 2012, 2001, 2000; CORACINI, 1995).
Keywords: flash fiction; reading; interpretation; sense effects